SIFAT MAMPU NYALA DAN MASSA OPTIMUM REFRIGERAN CAMPURAN R-290/R-22 SEBAGAI ALTERNATIF PENGGANTI R-22 - Ari D Pasek; Aryadi Suwono; Novianti Nugraha; Usman Rosyadi (Mesin, 2007)
The limited application of ozone depleting substance (ODS) such as CFC and HCFC refrigerants has encourage researchers to find a new alternative refrigerant. Hydrocarbon refrigerant such as R-290 (propane) has been widely used because it is environmentally friendly, save energy, and drop-in substitute. However, hydrocarbon refrigerants are flammable and categorized as A3 class refrigerant, so that the application of the refrigerants are limited by safety standard. In this research, an effort to lower the flammability of R-290 has been carried out. Series of flammability test have been done to proof that the flammability of R-290 is reduced by mixing it with R-22. Mixture of R-290/R-22 at molar fraction 0.4/0.6, 0.5/0.5, 0.59/0.41 has Lower Flammability Limit (LFL) above 3.5%, so that it can be classified as A2 class refrigerant. The optimum refrigerant charges of the refrigerant mixtures that give the highest COP have also been investigated. The results show that the optimum refrigerant charge of the mixture is lower than R-22 but higher than pure R-290. The system COP of R-290/R-22 mixture is higher than that of R-22 but lower than R- 290 system.